How do you factor #x^6 - x^4 - 2x^2 + 2#?

1 Answer
Jun 12, 2015

Answer:

Factor by grouping, then using difference of squares three times to find:

#x^6-x^4-2x^2+2#

#= (x^4-2)(x^2-1)#

#=(x-root(4)(2))(x+root(4)(2))(x^2+sqrt(2))(x-1)(x+1)#

Explanation:

In the following, we first factor by grouping then use the difference of squares identity:

#a^2-b^2 = (a-b)(a+b)#

up to three times...

#f(x) = x^6-x^4-2x^2+2#

#=(x^6-x^4)-(2x^2-2)#

#=x^4(x^2-1)-2(x^2-1)#

#=(x^4-2)(x^2-1)#

#=(x^4-2)(x-1)(x+1)#

If we allow irrational coefficients we can break this down some more using difference of squares a couple more times...

#=((x^2)^2-(sqrt(2))^2)(x-1)(x+1)#

#=(x^2-sqrt(2))(x^2+sqrt(2))(x-1)(x+1)#

#=(x^2-(root(4)(2))^2)(x^2+sqrt(2))(x-1)(x+1)#

#=(x-root(4)(2))(x+root(4)(2))(x^2+sqrt(2))(x-1)(x+1)#

There are no simpler linear factors with real coefficients since:

#x^2 + sqrt(2) >= sqrt(2) > 0# for all #x in RR#